Fowler Central Slip Tenotomy or Spiral Oblique Retinacular Ligament Reconstruction? A Cadaveric Biomechanical Study in Swan-Neck Deformity. (September 2020) - Deml, Christian; Baradaran, Aslan; Chen, Neal; Nasr, Michael; Kachooei, Amir R.
Background: The goal of this study is to biomechanically compare Fowler central slip tenotomy with spiral oblique retinacular ligament (SORL) reconstruction in correcting a chronic mallet deformity as part of a swan-neck deformity.Methods: We used 24 human cadaver fingers from 6 hands. Mallet finger and swan-neck deformities were created; then, Fowler tenotomy was done on one group including 3 hands with 12 fingers, and SORL reconstruction was done on the others.Results: During simulated finger extension, there was no significant difference between the 2 techniques in correcting the distal interphalangeal joint droop; however, Fowler tenotomy resulted in hyperflexion of the proximal interphalangeal (PIP) joint, whereas it remained straight after SORL reconstruction.Conclusions: This study supports the SORL reconstruction in correcting a chronic mallet deformity, especially when there is a concomitant PIP hyperextension deformity, which lowers the risk of reversing the deformity after a Fowler procedure.